2019
DOI: 10.1002/jcp.28751
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide microRNA screening reveals miR‐582‐5p as a mesenchymal stem cell‐specific microRNA in subchondral bone of the human knee joint

Abstract: Emerging evidence suggests that microRNAs (miRNAs) may be pathologically involved in osteoarthritis (OA). Subchondral bone (SCB) sclerosis is accounted for the knee osteoarthritis (KOA) development and progression. In this study, we aimed to screen the miRNA biomarkers of KOA and investigated whether these miRNAs regulate the differentiation potential of mesenchymal stem cells (MSCs) and thus contributing to SCB. We identified 48 miRNAs in the blood samples in KOA patients (n = 5) through microarray expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 43 publications
(64 reference statements)
0
22
0
Order By: Relevance
“…Basal level autophagy plays an important role in cellular homeostasis through the elimination of damaged organelles and aggregated intracellular proteins [16]. On the other hand, during conditions of cellular stress, such as nutrient deprivation/starvation, hypoxia, pathogen infection, radiation or anticancer drug treatment, the level of autophagy is augmented, resulting in adaptation and cell survival (cytoprotective response) [17]. Cartilage degeneration and cell death caused by autophagy inhibition play a crucial role in the process of OA [18].…”
Section: Introductionmentioning
confidence: 99%
“…Basal level autophagy plays an important role in cellular homeostasis through the elimination of damaged organelles and aggregated intracellular proteins [16]. On the other hand, during conditions of cellular stress, such as nutrient deprivation/starvation, hypoxia, pathogen infection, radiation or anticancer drug treatment, the level of autophagy is augmented, resulting in adaptation and cell survival (cytoprotective response) [17]. Cartilage degeneration and cell death caused by autophagy inhibition play a crucial role in the process of OA [18].…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies showed that in OA, several miRNAs could regulate the abnormal remodeling of the subchondral bone (Prasadam et al 2016; Liu et al 2019; Wang et al 2019; Zhao et al 2019). The present results revealed that miR-29b plays an important role in the regulation of the BMSC-mediated subchondral bone loss during TMJ-OA, which agreed with the results of previous studies and accordingly showed that miR-29b in BMSCs is multifunctional in different physiologic or pathologic conditions (Kaneto et al 2014; Liu et al 2015; Le et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…C3H10T1/2, MC3T3-E1 and ATDC5 are murine mesenchymal stem cells, preosteoblast and prechondrocyte cell-lines, respectively, that are commonly employed in various in vitro studies, interrogating the mechanisms underlying osteoblast and chondrocyte differentiation, bone disorders and repair (Hino et al, 2018;Lee et al, 2017;Wang et al, 2019;Yao & Wang, 2013). Despite the wide use of these cell-lines, how ciliary features vary in them during native OS and CH differentiation has not been so far investigated.…”
Section: Introductionmentioning
confidence: 99%